All-Inside Knee Arthroscopic Repair Outcomes in Mongolia, Effectiveness and Challenges - Togtmol, Munkhsaikhan; Sukhbaatar, Batsukh; Nachin, Baasanjav; Ochir, Chimedsuren (Central Asian Journal of Medical Sciences, 2021)
Objectives: We investigated the clinical outcomes of a few initial cases of interior knee arthroscopic surgical repair conducted in Ulaanbaatar, Mongolia. Methods: Arthroscopic knee repair patients were recruited into a single-arm trial study and followed up to the third month post-surgically. Subjects were the first cohort of all-inside arthroscopic knee surgery at the National Trauma and Orthopedics Research Center (NTORC) of Mongolia. We examined the subjects by tests including MRI prior to surgery, and complete knee evaluation including symptoms, functionality, and local examinations at the baseline and the third month after surgery. Pairwise statistical methods including McNemar Test and T-test were used. Additionally, Pearson’s R Correlations tests were used. Results: Forty-nine knee arthroscopic surgery patients were included for analysis. Knee pain, some local symptoms during recovery, and functionality significantly improved post-surgically, (p < 0.051). Arthroscopic knee interventions including anterior cruciate ligament reconstruction, local partial meniscectomy, and meniscal repair were predominantly conducted, strongly reflecting the knee MRI scan findings. Surgical site infections were absent in this cohort of patients. Age was correlated with post-surgical pain (p < 0.050). Conclusion: Knee arthroscopic outcomes for symptom alleviation and recovery of function were satisfactory at 3 months of follow-up in this study. We conclude that we enjoyed an excellent experience with all-inside knee arthroscopy in a central Asian lower-middle income country (LMIC) setting with younger and middle-aged patients. Older age Mongolians may present with post-surgical pain more often than these subjects.